Familial clustering of multiple sclerosis in a northern Swedish rural district. Issue 4 (April 1994) - Binzer, M; Forsgren, L; Holmgren, G; Drugge, U; Fredrikson, S
Abstract : A small rural district in the most northerly province of Sweden was found to have a very high occurrence of multiple sclerosis. A total of 12 patients with multiple sclerosis among 4744 inhabitants were identified (five females, seven males), corresponding to a prevalence of 253/100, 000. Many of the patients were related and a further 21 cases with multiple sclerosis (14 females, seven males), mostly living in the neighbouring area, have family ties to the district. A genealogical investigation showed that 22 of the 33 patients identified had ties of kinship and thus, to our knowledge, the largest aggregation of multiple sclerosis in a family is presented.